A multivariate calibration procedure for UV/VIS spectrometric monitoring of BHK‐21 cell metabolism and growth. (30th December 2013) - Leme, Jaci; Fernández Núñez, Eutimio Gustavo; de Almeida Parizotto, Letícia; Chagas, Wagner Antonio; dos Santos, Erica Salla; Caricati, Aline Tojeira Prestia; de, Alexandre Gonçalves; da, Bruno Labate Vale; Monteiro, Daniela Cristina Ventini; Boldorini, Vera Lucia Lopes; Jorge, Soraia Attie Calil; Astray, Renato Mancini; et al.
<x xml:space="preserve">Abstract</x> Monitoring mammalian cell culture with UV–vis spectroscopy has not been widely explored. The aim of this work was to calibrate Partial Least Squares (PLS) models from off‐line UV–vis spectral data in order to predict some nutrients and metabolites, as well as viable cell concentrations for mammalian cell bioprocess using phenol red in culture medium. The BHK‐21 cell line was used as a mammalian cell model. Spectra of samples taken from batches performed at different dissolved oxygen concentrations (10, 30, 50, and 70% air saturation), in two bioreactor configurations and with two strategies to control pH were used to calibrate and validate PLS models. Glutamine, glutamate, glucose, and lactate concentrations were suitably predicted by means of this strategy. Especially for glutamine and glucose concentrations, the prediction error averages were lower than 0.50 ± 0.10 mM and 2.21 ± 0.16 mM, respectively. These values are comparable with those previously reported using near infrared and Raman spectroscopy in conjunction with PLS. However, viable cell concentration models need to be improved. The present work allows for UV–vis at‐line sensor development, decrease cost related to nutrients and metabolite quantifications and establishment of fed‐batch feeding schemes. © 2013 American Institute of Chemical Engineers Biotechnol. Prog., 30:241–248, 2014